Community geography : GIS in action - English, Kim.; Feaster, Laura S. (Redlands, Calif. : ESRI, 2003)
Provides real case studies, hands-on exercises, and practical tips for using geographical information systems to learn about and make a difference in one's own community.
Includes bibliographical references p. [265-269].
Keywords: Geographic information systems -- Juvenile literature; Geographic information systems; Geography